Glucagon-Like Peptide-1 Receptor Regulates Macrophage Migration in Monosodium Urate-Induced Peritoneal Inflammation - Chen, Jun; Mei, Aihua; Liu, Xinxin; Braunstein, Zachary; Wei, Yingying; Wang, Biao; Duan, Lihua; Rao, Xiaoquan; Rajagopalan, Sanjay; Dong, Lingli; Zhong, Jixin (Frontiers in Immunology, 2022)
Glucagon-like peptide-1 (GLP-1) is an insulinotropic peptide that signals through the GLP-1 receptor (GLP-1R). GLP-1R, therefore, plays a critical role in diabetes and cardiovascular disease. Whether GLP-1R is involved in inflammatory disease such as gout remains unclear. Macrophages are critical effector cells in the pathogenesis of gout, a common form of inflammatory arthritis caused by the deposition of uric acid in joints. The expression of GLP-1R at the protein level is controversial due to the lack of specificity of existing antibodies against GLP-1R. Using a transgenic mouse model expressing enhanced green fluorescent protein (EGFP) under the control of GLP-1R promoter, here we confirmed the expression of GLP-1R by macrophages. M2 type macrophages and Ly6C+ macrophages expressed higher levels of GLP-1R, compared to their counterparts. GLP-1R deficient macrophages displayed a reduced the migratory ability and an enhanced expression of interleukin (IL)-6, while the expression of IL-1β was not affected. In monosodium urate (MSU) crystal-induced peritonitis, an experimental model of gout, the recruitment of macrophages, especially M2 macrophages, was significantly suppressed in GLP-1R knockout mice compared to wild-type mice. In conclusion, our data suggests that GLP-1R plays a critical role in macrophage migration in MSU-induced inflammation.